How P‐Wave Scattering Throughout the Entire Mantle Mimics the High‐Frequency Pdiff and Its Coda - Tuo Zhang; Christoph Sens‐Schönfelder; Marcelo Bianchi; Klaus Bataille (Geophysical Research Letters)
Abstract We document the arrival of seismic energy in the core shadow zone up to large distances beyond 150° more than 100 s prior to the core phases. Numerical simulations of the energy transport in an established heterogeneity model show that scattering throughout the entire mantle explains these observations. Diffraction at the core‐mantle boundary is unlikely in our 1–2 Hz frequency band and is not required indicating misleading terminology with reference to Pdiff for the scattered P∗P‐energy. Records of the largest deep earthquakes at low‐noise stations are key to the observation of the faint precursory signal which changes appearance with increasing distance from a coda‐like decay over a constant amplitude level around 130° to an emergent wave train. According to our simulations, different depth layers in the mantle dominate different time‐distance windows of the scattered wave train, providing the opportunity to improve the depth resolution of mantle heterogeneity models.